In vitro effects of sodium nitroprusside and leptin on norepinephrine-induced vasoconstriction in human internal mammary artery - Burma, Oktay; Ozcan, Mete; Kacar, Emine; Uysal, Ayhan; Sahna, Engin; Ayar, Ahmet (Clinics Cardive Publ Pty Ltd, 2015)
Aim: The biological and pharmacological properties of vessels used in coronary artery bypass graft (CABG) surgery are as important as their mechanical properties. The aim of this study was to investigate the possible role of protein kinase C (PKC)-dependent mechanisms in leptin-induced relaxation in the human internal mammary artery (IMA). Methods: IMA rings, obtained from patients undergoing CABG surgery, were suspended in isolated tissue baths containing Krebs-Henseleit solution, which were continuously gassed with 95% O-2 and 5% CO2 at 37 degrees C. Results: The IMA rings were pre-contracted with increasing concentrations of norepinephrine (NE 10(-9)-10(-4) mol/l) and the relaxation responses to sodium nitroprusside (SNP), a nitrosovasodilator, and leptin were studied in the presence and absence of a PKC inhibitor. Leptin (1 mu M) caused a dose-dependent relaxation in NE pre-contracted IMA rings. Pre-treatment with a PKC inhibitor significantly attenuated this vasorelaxatory response to leptin in human isolated IMA. Conclusion: It was found that SNP and leptin caused significant relaxation of the NE pre-contracted human IMA rings, and PKC was probably the sub-cellular mediator for this effect. Our findings may have clinical or pharmacological importance as it could be hypothesised that obese subjects who have a left IMA bypass graft would have better myocardial perfusion.
Keywords: internal mammary artery; leptin; contraction; protein kinase C; norepinephrine; sodium nitroprusside